Cloning and characterization of a novel NAD+‐dependent glyceraldehyde‐3‐phosphate dehydrogenase gene from Candida glycerinogenes and use of its promoter. Issue 4 (12th March 2013) - Zhang, Cheng; Zhuge, Bin; Zhan, Xiaobei; Fang, Huiying; Zong, Hong; Zhuge, Jian
Abstract A 3950 bp genomic fragment from Candida glycerinogenes, WL2002‐5, containing the CgGAP gene encoding a glyceraldehyde‐3‐phosphate dehydrogenase homologous to GAP genes in other yeasts using degenerate primers, was cloned and characterized with inverse PCR. Sequence analysis revealed a 1164 bp open reading frame encoding a putative peptide of 387 deduced amino acids, with a molecular mass of 36 kDa. The CgGAP protein consisted of an N‐terminal NAD+‐binding domain and a central catalytic domain. Six stress‐response elements were found in the upstream region of the CgGAP gene. The influence of CgGAP on glycolysis was investigated. Functional analysis revealed that Saccharomyces cerevisiae transformed with CgGAP was restored to the wild‐type phenotype when cultured in high‐osmolarity medium, suggesting that it is a functional GAP protein. Promoter studies in S. cerevisiae using the green fluorescent protein (gfp) gene as a reporter showed that the GAP promoter (PCgGAP) is constitutively expressed in S. cerevisiae cells grown on glucose. Copyright © 2013 John Wiley & Sons, Ltd.